Determinant of customer intention to adopt mobile banking services in Sauda Arabia - Alsheikh, Layla Hodaed (2013)
Mobile technologies and services create a wide spectrum of business opportunities. Despite the availability of technologically advanced mobile devices, mobile banking services have not been widely accepted by bank customers. The purpose of this study is to examine the major factors that contribute towards customer’s intention to adopt mobile banking. In addition, the study aims to examine the direct and indirect effects of perceived value on behavioural intention. This research uses primary data and the unit of analysis is individuals who are nonuser of mobile banking services. The study questionnaires were distributed to samples throughout Saudi Arabia with emphasis on major cities. Four hundred and three valid responses were received and analysed through multivariate analysis process using Structural Equation Modelleing (SEM) via Analysis of Moment Structures (AMOS) software. The findings of the research demonstrate four main results. First, mobile phone experience and awareness of service have a strong positive influence on benefit factors (performance expectancy, effort expectancy). Second, the findings show that benefit factors have significant and positive impact on perceived value. Third, the results also reveal that performance expectancy, effort expectancy, perceived risk and perceived value are significant predictors of intention to use mobile banking in the initial adoption stage. Fourth, the findings indicate that perceived value significantly mediates the relationship between benefit factors (performance expectancy, effort expectancy) and behavioural intention. Several managerial and policy implications for Saudi commercial banks and Saudi Arabia Monetary Agency are presented which affect their on-going campaigns about information security of banking transactions through electronic banking channels. The study shows that mobile phone experience and awareness of service are critical in the comprehension of the technology and the related functionality and benefits while the lack of knowledge and information maximize the perception of risk. The principal conclusion is that mobile banking services have to demonstrate to the bank customer its uniqueness compared to other competing services in the same category (electronic banking services). Differentiation can be achieved by having more benefit factors than sacrifice factors (perceived cost, perceived risk) that can create perceived value for adopting mobile banking services in the future. Once the bank customers assess the mobile banking services based on their perceptions of what is received and what is given, they start to make decision that will influence behavioural intention to adopt or not to adopt mobile banking services.